UPAYA MENINGKATKAN KEMAMPUAN OPERASI HITUNG PECAHAN MENGGUNAKAN MODEL PEMBELAJAAN DIRECT LEARNING PADA SISWA KELAS V SDN SUKASARI 2 - Retnaningtyas, Dian; Suparman, Tarpan; Fitri, Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of the research is to analyze the increase in mathematical skills in fraction calculation operation material for class V students at Sukasari 2 National Elementary School using the direct learning method, because of the importance of problem solving skills in mathematics education. The research method used is a descriptive qualitative method. Determining the subjects of this research used a purposive sample. This research provides a detailed analysis of each student's performance on the problem-solving ability test and interviews are also conducted with students to validate the research results. From the results of the fraction calculation operation ability test of 25 students in class V of Sukasari 2 Elementary School, it was found that 44% of students had results in the